Mechanical properties of tef starch based edible films: Development and process optimization. Issue 2 (February 2023) - Tafa, Kenenisa Dekeba; Satheesh, Neela; Abera, Worku
Abstract: The non-biodegradable synthetic plastic is one of the greatest challenges facing the food packaging business since it seriously harms the environment. To solve this problem, non-biodegradable plastic may be disposed of more affordably and with less harm on the environment by using edible starch-based biodegradable film. Therefore, the present study was focused on the development and optimization of tef starch based edible films based on mechanical properties. In this study response surface methodology was employed by considering 3–5g of tef starch, 0.3–0.5% of agar and 0.3–0.5% of glycerol. The prepared film showed the tensile strength of 17.97–24.25 Mpa, elongation break of 1.21–2.03%, elastic modulus of 17.58–108.69 MPa, puncture force of 2.55–15.02 N, puncture formation of 9.59–14.95 mm. The findings showed that as glycerol concentrations in the film-forming solution increased, the prepared tef starch edible films' tensile strength, elastic modulus, and puncture force declined while their elongation at break and puncture deformation increased. Tef starch edible films' mechanical characteristics, including as tensile strength, elastic modulus, and puncture force, were increased by the increase of agar concentration. The optimized (from 5 gm tef starch, 0.4 g agar and 0.3% glycerol) tef starch edible film exhibited higher tensile strength, elastic modulus, and puncture force while lower elongation at break and puncture deformation. The composite edible film based tef starch with agar exhibited good mechanical properties and can be suggested for application in food industry as food packaging.